The Role of Risk Management in Minimizing Delayed Payment of Receivables at PT Alam Mulya - Sri Trisnaningsih; Adinda Puspita Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Late payment of accounts receivable is a serious challenge that can disrupt the stability of the company's cash flow and financial performance. This study aims to evaluate the role of risk management in minimizing late payment of accounts receivable at PT Alam Mulya, a logistics company in Surabaya. The research method used is descriptive qualitative with a case study approach, through direct observation, interviews, and documentation during the five-month internship period. The results showed that the company has implemented risk management principles, such as customer identification, setting credit limits, monitoring maturity, and implementing active collection. However, the implementation has not been thorough and consistent, especially in the aspects of using digital systems, documenting credit policies, and applying sanctions for late payments. It was also found that decision interventions based on personal relationships hindered the effectiveness of risk control. This study recommends the implementation of an integrated digital system, the establishment of a written credit policy, and staff training related to risk management and collection. By strengthening comprehensive risk management, the company is expected to improve the efficiency of receivables management and maintain optimal cash flow sustainability.